Informe de pasantía en el área comercial de la empresa Obleas Dominguez S.A.S (2020)
The purpose of this report is to present the final result of the internship, a prerequisite for aspire to the title of professional in International Trade that was carried out in the commercial area of ​​the company OBLEAS DOMINGUEZ S.A.S. The duration of the internship meet rigorously all the academic training objectives required by the Antonio University Nariño and with the organization's policies.